Composition of Catch Results from Gombang Fishing Tools in Prapat Tunggal Village, Bengkalis District, Riau Province - Desi Mahrani; Jonny Zain; Isnaniah Isnaniah (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
One of the livelihoods of the people of Prapat Tunggal Village, Bengkalis Regency, Riau Province, is fishing. The fishing gear fishermen operate is longline, gombang, drier, and gill nets. The research was conducted in June to determine the composition of catches from gombang fishing gear in Prapat Tunggal Village. The method used is a survey method and descriptive analysis. From the results of this research, the number of catches from gombang fishing equipment was 153.77 kg or 433,290 fish. The dominant net is rebon shrimp, which is the main catch of 77.90% of the total weight of the trap and the bycatch catch of 20.92%, as well as the discard catch of 1.17%.